Is quality a strategy or an operation?. Issue 7 (2nd July 2019) - Toussaint, John Stephen; Mead, Elaine
Abstract : Traditional healthcare management needs an overhaul. Medical errors have become a norm and costs continue to escalate. A new management philosophy is emerging at a few NHS Trusts. Recent research has shown that operational excellence, the management approach described in this article, leads to improved patient cost and quality outcomes. However, it requires healthcare leaders to behave and act differently. The approach is anchored by a standardised set of management practices that all managers and leaders need to follow. The authors will describe changes leaders have made and what impact these changes have on staff, patient, and organisational outcomes.